2017
DOI: 10.3892/or.2017.6139
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extract of Patrinia scabiosaefolia induces the death of human renal cell carcinoma 786-O cells via SIRT-1 and mTOR signaling-mediated metabolic disruptions

Abstract: Recently, natural plant extracts have shown tremendous potential as novel antitumor drugs. Patrinia scabiosaefolia, a traditional prescription for inflammatory diseases, has been reported to effectively suppress various types of cancers. However, the mechanisms underlying its antitumor properties remain elusive. In the present study, we investigated the antitumor effects of an ethanol extract of Patrinia scabiosaefolia (EPS) on human renal cell carcinoma 786-O cells. After 24 h of incubation with EPS, the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…At the dose of 0.6 or 1 mg/mL, it markedly increased the levels of intracellular ROS and Ca 2+ , and significantly down-regulated the expression of SIRT-1 and reduced the ratio of pmTOR/mTOR. PS Li et al (2018) CRC mouse xenograft model (negative control: saline), HT-29 (negative control: culture solution) ethanol extract (500 g PS was extracted by refluxing with 5000 mL 85% ethanol and filtered. The ethanol solvent was concentrated by rotary evaporation to a relative density of 1.05.…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…At the dose of 0.6 or 1 mg/mL, it markedly increased the levels of intracellular ROS and Ca 2+ , and significantly down-regulated the expression of SIRT-1 and reduced the ratio of pmTOR/mTOR. PS Li et al (2018) CRC mouse xenograft model (negative control: saline), HT-29 (negative control: culture solution) ethanol extract (500 g PS was extracted by refluxing with 5000 mL 85% ethanol and filtered. The ethanol solvent was concentrated by rotary evaporation to a relative density of 1.05.…”
Section: Pharmacologymentioning
confidence: 99%
“…In addition, it significantly inhibited SIRT-1 and mTOR signaling. Therefore, Li et al (2018) believed that the ethanol extract of PS induces the death of 786-O cells through metabolic disorders mediated by SIRT-1 and mTOR signaling. On the other hand, the studies on anti-cancer effect of ethanol extract of PV were relatively less.…”
Section: Pharmacologymentioning
confidence: 99%
“…The analysis of the transcriptomes of TCGA KIRC patients showed that there is a strong correlation between abnormal sirtuin and HDAC expression levels and the mTOR pathway. A recent study found that the ethanol extract of Patrinia scabiosaefolia induces the death of human renal cell carcinoma 786-O cells via SIRT1 and mTOR signaling-mediated metabolic disruptions [ 52 ]. SIRT5-mediated SDHA desuccinylation promotes clear cell renal cell carcinoma tumorigenesis [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Western blotting was performed as described previously 48,49 . Cells were lysed using RIPA buffer with Phenylmethanesulfonyl fluoride and phosphatase inhibitors, and total proteins were extracted after transfection.…”
Section: Western Blot Analysismentioning
confidence: 99%